2020
DOI: 10.3390/admsci10010008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Monetary Incentives: Bonus and/or Stimulus

Abstract: In this paper, the role of the monetary incentives in the employee performance is investigated in the context of Public Administration (PA). In particular, the distribution of monetary incentives among the employees based on the position held, is compared with a merit approach which tends to recognize and reward individual contributions. Starting from a questionnaire, the informal network, which ignores the vertical relation among supervisor and employees, is created and a Centrality Index, based on the employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…e design of both employees' performance evaluation and monetary incentives distribution have been presented and discussed according to the theoretical and computational aspects. e results have shown a modification of the employee's behavior according to both the theoretical foundations and the results discussed in [89,90]. Both the empirical and computational results show that the monetary incentives work as stimulus for employees to reach the maximum incentive and the mechanism is suitable during the years.…”
Section: Discussionmentioning
confidence: 79%
“…e design of both employees' performance evaluation and monetary incentives distribution have been presented and discussed according to the theoretical and computational aspects. e results have shown a modification of the employee's behavior according to both the theoretical foundations and the results discussed in [89,90]. Both the empirical and computational results show that the monetary incentives work as stimulus for employees to reach the maximum incentive and the mechanism is suitable during the years.…”
Section: Discussionmentioning
confidence: 79%
“…Incentives represent another important coordination mechanism of mesovertical specialization. There exist different ways in which incentives may be implemented, from monetary ones [57,58] to the possibility of hierarchical growth and the increased perception of one's contribution to overall organizational output [59,60]. Artificial intelligence will presumably play a significant role in the definition of one specific incentive.…”
Section: Coordination Mechanisms Of Meso-organizational Specialization Standardization Formalization and Incentivesmentioning
confidence: 99%
“…According to the author, if enterprises want to achieve success in a competitive environment, they should value their workers. Another study, conducted by Ponta et al(2020) suggested that the bonuses of enterprises must be flexible, suitable for each object and the achievements that workers contribute, meeting expectations. The effect of bonuses on labor productivity is significant.…”
Section: Bonuses and Labor Productivitymentioning
confidence: 99%
“…The bonus scale is also measured by workers' perception. The bonus scale is inherited from the previous scale (Bun & Huberts, 2018;Ponta et al, 2020).…”
Section: Bonus Scalementioning
confidence: 99%